Nonlinear Dynamics of a Reduced Cracked Rotor - Lu, K.; Lu, Y.; Zhou, B. C.; Jian, W.; Yang, Y. F.; Jin, Y. L.; Chen, Y. S. (Journal of Vibration Testing and System Dynamics, 2026)
The transient proper orthogonal decomposition (TPOD) method is applied for order reduction in the rotor system in this paper. A 26-DOFs rotor model with crack is established by the Newton’s second law, and the dynamical behaviors (bifurcation diagram, mplitude frequency curve, etc.) of the crack fault are discussed. The optimal reduced model can be provided by the proper orthogonal mode (POM) energy method, the TPOD method is applied to reduce the original system to a three-DOFs one at a certain speed corresponds to the maximum energy. The efficiency of the TPOD method is verified via comparing with the bifurcation diagram of the original and reduced rotor system. The order reduction method provides qualitative analysis to study the reduced model of the high-dimensional rotor system.